1987
DOI: 10.1177/135945758700100205
|View full text |Cite
|
Sign up to set email alerts
|

Music Therapy in a General Hospital's Psychiatric Unit — A ‘Pilot’ Evaluation of An Eight Week Programme

Abstract: Within Great Britain music therapy is developing a presence in the field of mental health. There is a history of work within the large institutions and there are present moves to develop more work in community based day hospitals and units. This paper charts the setting-up of a short period of eight sessions for a group attending a unit based within a general hospital. Positive results from a simple evaluation from both clients and staff point to the need for further studies to be set up when more detailed que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The integration of music therapy within the models and systems of the institutional setting meant prioritization of multidisciplinary team communication, provision of clear information to both patients and staff, and provision of a programme to maximize patient access and staff support [34], [40], [75], [91], [104]. Solli [108] suggests therapists tailor their work at different individual, group, ward and hospital levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The integration of music therapy within the models and systems of the institutional setting meant prioritization of multidisciplinary team communication, provision of clear information to both patients and staff, and provision of a programme to maximize patient access and staff support [34], [40], [75], [91], [104]. Solli [108] suggests therapists tailor their work at different individual, group, ward and hospital levels.…”
Section: Resultsmentioning
confidence: 99%
“…Low attendance was generally experienced negatively by patients [50], [91] and impacted upon the group dynamic [117]. Access to sessions was limited by mental state, external events or by institutional barriers such as the time taken for referral and assessment and ongoing demands upon the patient whilst in hospital [34], [52]. Talwar et al [116] also observed that uptake of outpatient attendance was rare unless several in-patient sessions were attended.…”
Section: Resultsmentioning
confidence: 99%
“…Throughout, the use of music is professional in its approach, notwithstanding the lack of formally qualified music therapists or psychotherapists with a musical background being employed in the project (and contrary to the different trends evident in customary music therapy: cf. Bunt, Pike & Wren, 1987;Bunt, 1997). In Florence, children exercise considerable control of the musical intervention, deciding whether they want it (or not) and for how long the musical activity should last.…”
Section: Introductionmentioning
confidence: 99%